Functions and transformations

Functions can be used to describe transformations of the graph y = f(x).

f(x) + a is the same as a translation of a up and can be described by the vector begin{pmatrix} 0 \ a end{pmatrix}

Let’s use f(x) = x^2 + 2x - 3 as an example. Here is a graph of y = f(x)

Now we will graph y = f(x) + 3 which is the same as a translation of begin{pmatrix} 0 \ 3 end{pmatrix}

f(x) - a is the same as f(x) + (-a) and so is a move of -a upwards, or in other words, a move of a downwards. The translation can be described by the vector begin{pmatrix} 0 \ -a end{pmatrix}

f(x + a) is a move left by a. The translation can be described by the vector begin{pmatrix} -a \ 0 end{pmatrix}

Let’s use f(x) = x^2 + 2x - 3 as an example again. Then f(x + 3) = (x+3)^2 + 2(x + 3) - 3

=(x+3)(x+3) + 2x + 6 - 3

=x^2 + 6x + 9 + 2x + 3

=x^2 + 8x + 12

Below is a plot of f(x) and f(x+3)

f(x - a) is the same as f(x + (-a)) and so is a move of -a left, or in other words, a move of a right. The translation can be described by the vector begin{pmatrix} a \ 0 end{pmatrix}

-f(x) is the same as a reflection in the x-axis.

Let’s use f(x) = x^2 + 2x - 3 as an example again. Then -f(x) = -(x^2 + 2x - 3) = -x^2 - 2x + 3

f(-x) is the same as a reflection in the y-axis.

Let’s use f(x) = x^2 + 2x - 3 as an example again. Then f(-x) = (-x)^2 + 2(-x) - 3 = x^2 - 2x - 3